Efecto de la concentración de HC1 y tiempo de hidrólisis en el rendimiento de glucosa para la obtención de bioetanol a partir de almidón de manihot esculenta yuca dulce - De La Cruz Zegarra, Anthony Rafael (2017)
This project obtained an anhydrous ethyl alcohol fuel from starch cassava (Manihot esculenta), evaluating the effect of the concentration of HCl and reaction times of process hydrolysis, achieving to obtain the greater conversion of glucose and therefore the greatest yield of alcohol. To achieve this began working with a starch concentration of 20%, supplied in the process of hydrolysis HCl doses to concentration of 0.7% to 2.7% and reaction times of 110 to 230 minutes. Applied in our experimental model a Central Compound Design Rotational (DCCR) of 22 points factorial, with 4 points axial and 3 repetitions in the central point through the software Statistica 8.0, which identified statistically significant effect between the concentration of HCl and reaction times in the process of hydrolysis. By using the methodology of surface response succeeded in identifying the optimal levels of the process of hydrolysis, being the concentration of HCl of 1.65 to 2.3% (v/v) and reaction time of 215 to 240 minutes, get the largest concentration of 19.7144 g/l (9.3645%) of glucose. The bioethanol yield anhydrous was 12.00%, being the efficiency in the fermentative process of 69.56%, in the process of distillation of 79.52%, in the operation of rectification of 82.56% and in the operation of purification of 71.19%, obtaining an absolute alcohol with purity of 99.9 ºGL